Reduced-order thermodynamic models for servo-pneumatic actuator chambers - J. Falcão Carneiro (2006)
This paper discusses thermodynamic models of air inside pneumatic actuator chambers. In servopneumatics common practice, these models are simplified by neglecting the temperature dynamics. Classical models in literature assume temperature inside the pneumatic chamber to be either constant or to follow a polytropic law. Furthermore, the mixing process of air entering the chamber and heat transfer between air and cylinder walls is often neglected or only implicitly taken into account. This work evaluates the impact of these simplifications/order reductions in the prediction of pressure inside the actuator chamber. Classical models are compared with several others taking into account not only the mixing process but also explicitly including heat transfer between air and cylinder walls. Simulation studies show that the reduced order models proposed in this paper can lead to a mean square error in pressure prediction of only 10% of the one obtained using classical models.